KOINTEGRASI BURSA-BURSA SAHAM DI ASIA - Riko Hendrawan; Teika Trikartika Gustyana (University of Merdeka Malang, 2011)
One important indicator of capital market development could be seen from the value of the composite stockprice index. Composite stock price index reflected the performance of all shares registered in particular country.The objective of this research was to know whether there was co integration or long-term equilibriumamong Indonesia, Malaysia, Singapore, Thailand, Philippines, Hongkong, Japan, South Korea and China,either in groups or in pairs using the method of co-integration during January 2000 - January 2010. Theresults of this research using Johansen Co-Integration test indicated that there was long-term equilibriumamong Indonesia, Malaysia, Singapore, Thailand, Philippines, Hongkong, Japan, South Korea and China inthe period of January 2000 - January 2010, in groups and in pairs. The results showed that the South Koreastock market was the most influential to the Indonesian stock markets, and Chinas stock market was the mostdominant stock market among these countries during January 2000 - January 2010.